Kajian Yuridis Transaksi Jual-Beli melalui Facebook Ditinjau dari KUHPerdata - Rahman Sofian; Ufran Ufran (Utan Kayu Publishing, 2023)
This research is aimed to know and comprehend the validity of sale and purchase transactions through facebook reviewed from the Civil Law and to understand the legal protection of the parties in the sale and purchase transactions through facebook in case of default. The type of research with qualitative analysis method that is collecting data based on quality relating to the issues discussed. The findings are: First: the sale and purchase transactions through facebook reviewed from the Civil Law considered valid because Law number 11 in the year of 2008 EIT based on Civil Law. Second: basically, the legal protection of the parties in the sale and purchase transactions through facebook in case of default has been guaranteed and protected by Law number 11 in the year of 2008 Electronic Information and Transaction, Civil Law, and Law number 8 in the year of 1999 Consumer Protection, and has evidence and postulate to prove that there are parties who have been disadvantage.